SOME PROBLEMS OF ELECTRICAL GEOPHYSICAL PROSPECTING METHODS USED FOR EXPLORATION OF ORE DEPOSITS - V. A. Kulikov; A. G. Yakovlev; V. A. Polikarpova (Геодинамика и тектонофизика)
Electrical geophysical prospecting methods are widely used at different stages of geological exploration. In the last two decades, new computer technologies and satellite navigation systems were successfully introduced in the geophysical industry. As a result, exploration technologies have improved, and new geophysical methods have been developed, such as electrical resistivity tomography (ERT) and spectral induced polarization (SIP) methods. An important role in ore geophysics is played by magnetotelluric (MT) methods. In this article, we focus on the issues of methodology and interpretation of electrical prospecting data for solving ore exploration problems. Special attention is paid to the induced polarization (IP) method that is most widely used in mineral exploration and mining industry as one of the most important and most dynamically developing techniques of ore geophysics. In addition, the issues of correct choices of survey scales and the use of automatic 2D and 3D inversion programs are considered.